Wittgenstein's notes on logic - Potter, Michael D. (Oxford : Oxford University Press, 2008)
Michael Potter shows, for the first time, that Wittgenstein's early 'Notes on Logic' are a work of philosophical and historical importance. Using a blend of biography and philosophy, he draws new conclusions about the nature of the notes, the genesis of the Tractatus, and Wittgenstein's working methods.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Logic